2022
DOI: 10.1186/s13613-021-00977-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Frailty Scale (CFS) indicated frailty is associated with increased in-hospital and 30-day mortality in COVID-19 patients: a systematic review and meta-analysis

Abstract: Background The concept of frailty provides an age-independent, easy-to-use tool for risk stratification. We aimed to summarize the evidence on the efficacy of frailty tools in risk assessment in COVID-19 patients. Methods The protocol was registered (CRD42021241544). Studies reporting on frailty in COVID-19 patients were eligible. The main outcomes were mortality, length of hospital stay (LOH) and intensive care unit (ICU) admission in frail and no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 106 publications
2
28
0
1
Order By: Relevance
“…As the pandemic advances, other investigations on the associations of frailty, organ support, and long-term survival in critically ill patients with COVID-19 might provide new insights. However, recent systematic reviews studying frailty in hospitalized COVID-19 patients demonstrated that all reports concern databases from 2020, similar to ours ( 3 , 27 ). And the association of the concept of frailty with ICU outcomes has been demonstrated before COVID-19 ( 23 ), highlighting that it is not specific to this infectious disease.…”
Section: Discussionsupporting
confidence: 86%
“…As the pandemic advances, other investigations on the associations of frailty, organ support, and long-term survival in critically ill patients with COVID-19 might provide new insights. However, recent systematic reviews studying frailty in hospitalized COVID-19 patients demonstrated that all reports concern databases from 2020, similar to ours ( 3 , 27 ). And the association of the concept of frailty with ICU outcomes has been demonstrated before COVID-19 ( 23 ), highlighting that it is not specific to this infectious disease.…”
Section: Discussionsupporting
confidence: 86%
“…It is well established that higher degrees of frailty have been associated with poor outcomes and higher mortality rates during and after ICU admission [38,39]. Similarly, we observed that hospital mortality increased with increasing frailty in both patients with and without COVID-19.…”
Section: Relationship To Previous Ndingssupporting
confidence: 79%
“…It is well established that higher degrees of frailty have been associated with poor outcomes and higher mortality rates during and after ICU admission [ 42 , 43 ]. Similarly, we observed that hospital mortality increased with increasing frailty in both patients with and without COVID-19.…”
Section: Discussionmentioning
confidence: 99%